2008
DOI: 10.1157/13115667
|View full text |Cite
|
Sign up to set email alerts
|

The view of patients with asthma or chronic obstructive pulmonary disease (COPD) on complementary and alternative medicine

Abstract: Most of the patients with asthma or COPD prefer alternative medicine. CAM use by patients with COPD should be asked about by their doctors, strongly advised about continuing their medicines and about side effects of CAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 11 publications
5
25
0
4
Order By: Relevance
“…reported that praying, breathing methods, relaxation techniques, natural products such as herbs and minerals, and massage were the most commonly used CAM methods in children with asthma. In two studies conducted in Turkey that are supporting our results, it has been reported that the most popular CAM methods were herbal remedies in asthma and COPD patients 17,18 . Additionally, in two studies regarding children with asthma in Turkey, 19,27 it has been reported that herbal products are one of most commonly used CAM methods.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…reported that praying, breathing methods, relaxation techniques, natural products such as herbs and minerals, and massage were the most commonly used CAM methods in children with asthma. In two studies conducted in Turkey that are supporting our results, it has been reported that the most popular CAM methods were herbal remedies in asthma and COPD patients 17,18 . Additionally, in two studies regarding children with asthma in Turkey, 19,27 it has been reported that herbal products are one of most commonly used CAM methods.…”
Section: Discussionsupporting
confidence: 86%
“…CAM usage in Turkey has been subject of only few studies. In these studies, the percentage of CAM usage varies between 33% and 52% 12–19 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] The prevalence of the use of CAM among adult asthmatic patients varies from 4-79%. [7] In Asia, little is known about the prevalence of the use of CAM among asthmatic patients.…”
mentioning
confidence: 99%